THE EFFECT OF COOPERATIVE LEARNING MODELS OF INVESTIGATION GROUP TYPE ON SCIENTIFIC ATTITUDES - Putri, N.K, Anggita; Wibawa, Citra; I.W, Widiana. (Universitas Pendidikan Ganesha, 2018)
The aim of this study is to find out the significant differences of scientific attitude between a group of students who is taught by cooperative learning in type of group investigation and a group of students who is taught by conventional learning. This study is quasi experiment with nonequivalent control group design and post test only design. The population of this study is the whole V grade students Gugus I in Buleleng Sub-district which is involving 149 students. The sample is taken randomly by using random sampling. The sample is 60 students from V grade students of SDN 3 Banyuning and SDN 2 Banyuning. Validation on scientific attitude instrument of content validity with Greogory test, grain validity using product moment and reliability with Alpha Cronbach.The data is taken by using questionnaire and analyze using descriptive statistics and inferential statistics analysis (T-test) with polled variant formula. The finding shows that the average score of post test group is 83,71 which belong to high category. Meanwhile, the average score of conventional group is 68,47 which belong to moderate category. The obtain result of T test is tcount = 9,99 belong to 5% significant from ttable = 2,000. In conclusion, tcount>ttable, with a result that H0 is rejected and H1 is accepted.It means that there was a significant difference in scientific attitudes between classes that were taught by cooperative learning model of group investigation type and classes that were taught by conventional learning model. Thus, cooperative learning model of group investigation type had a positive effect on students' scientific attitude.